EFEKTIFITAS EKSTRAK RIMPANG LENGKUAS DALAM MENGHAMBAT AKTIFITAS CENDAWAN Oncobasidium theobremae SECARA In-vitro - S, Ismail Suaib.; Lakani, Irwan; Panggeso, Johanis (AGROTEKBIS, 2016)
Vascular streak dieback disease caused by the fungus Oncobasidium theobremae is one of the important diseases of the cocoa crop. Galangal potential as a botanical pesticides that have various properties of them as anti-fungal and antibacterial. This study aims to determine the effectiveness of ginger rhizome extract in suppressing the activity of growing fungus O. theobremae. Implementation of the study began in August 2015 to February 2016 is located in the Laboratory of Plant Diseases, Faculty of Agriculture unit UNTAD sampling sites Salubomba disease in the village, District of South Banawa, Donggala, Central Sulawesi. This study uses galangal rhizome extract mixed with a concentration of 0.25%, 0.50% and 0.75% into the PDA (Potato Dextrose Agar). The results of the study during the week of observation showed that the highest concentration (0.75%) were able to inhibit the development of fungus O. theobremae with a percentage of 38.77%.Â Key Words : Ginger extract , concentration, Cocoa, and O. theobremae.Â